Sustainability and water management in the Maya world and beyond - Larmon, Jean T., 1988-; Lucero, Lisa Joyce, 1962-; Valdez, Fred, Jr., 1953- (University Press of Colorado, 2022)
"Investigates climate change and sustainability through time, exploring how political control of water sources, maintenance of sustainable systems, ideological relationships with water, and fluctuations in water availability have affected and been affected by social change"--